Efisiensi Saluran Pemasaran Ikan Tongkol Hasil Tangkapan Nelayan di Pangkalan Pendaratan Ikan Oeba Kota Kupang - Melkianus Teddison Bulan; Saulus Mendario (2339-1324, 2025)
This study aimed to determine the marketing channel pattern of fishermen-caught tuna at the Oeba Fish Landed Base (FLB) of Kupang City, analyze the amount of margin received by each marketing institution of fishermen-caught tuna at the Oeba Fish Landing Base (FLB) of Kupang City, and analyze the efficiency of the marketing channel of fishermen-caught tuna at the Oeba Fish Landing Base (FLB) of Kupang City. The type of research used in this study was descriptive. The population in this study amounted to 59 people and the sampling of marketing institution respondents was carried out by snowball sampling so that all populations were sampled. The findings showed that the marketing channel pattern of tuna caught by fishermen at the Oeba Fish Landing Base (FLB) in Kupang City was leveled I marketing channel (fishermen - retail traders - consumers) and leveled II marketing pattern (fishermen - intermediary traders - retail traders - consumers), the amount of marketing margin received in leveled I marketing channel, which is the difference between consumer prices and fishermen of Rp 7.500, and leveled II marketing channel, the price difference between fishermen to retailers is Rp 2.500 and retailers to consumers is Rp 7.500, and level I and level II tuna marketing channels at the Oeba Fish Landing Base (FLB) in Kupang City was classified as effective.